DEVELOPMENT OF STUDENT MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION - Nurlathifah, Luthfiana; Lisartika, Mia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
High quality education is considered the main target in every education system. The development of management training participants is a very crucial component in achieving this target. Student management Refers to systematic efforts to manage and facilitate student growth and development in the educational environment. This research explains the concept of student management development. Regarding the method determined in this research, it uses library research which discusses the development of student management in improving the quality of education. The results of this research indicate that developing student management is an important effort to improve the quality of education. By managing students effectively, schools can create a learning environment that supports and supports the growth and development of students holistically. Even though there are challenges in developing student management, the efforts made to improve the quality of student management are very important to achieve optimal educational goals. The use of technology in student management can improve the quality of education